2014
DOI: 10.1007/s10725-014-9949-1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating multifaceted urease producing marine Pseudomonas aeruginosa BG as a cogent PGPR and bio-control agent

Abstract: Species belonging to the genus of Pseudomonas are known to possess metabolic versatility and are capable of adapting to various environments. One such strain BG, possessing urease activity, was isolated from marine water from the Gulf of Khambhat, Gujarat. 16S rRNA gene sequence analysis was performed to identify the isolate, which showed that it was the closest neighbor to be Pseudomonas aeruginosa strain BS8. Strain BG was accessed (meant to be assessed?) for multiple plant growth promoting and biocontrol tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…In the genus Pseudomonas , species such as P . fluorescens (isolated from soil) and P. aeruginosa (isolated from ocean) possess urease activity (Jyothi and Umamahe, 2013 ; Goswami et al, 2015 ). In addition, two Streptococcal species, S. thermophiles and S .…”
Section: Discussionmentioning
confidence: 99%
“…In the genus Pseudomonas , species such as P . fluorescens (isolated from soil) and P. aeruginosa (isolated from ocean) possess urease activity (Jyothi and Umamahe, 2013 ; Goswami et al, 2015 ). In addition, two Streptococcal species, S. thermophiles and S .…”
Section: Discussionmentioning
confidence: 99%
“…These results agreed with Zimmer and Bothe [42] that designated that tryptophan is the precursor of IAA biosynthesis and used to stimulate its production. IAA is responsible for the improvement of plant growth by motivation of apical dominance and development of a highly organized root system by which uptake of nutrients becomes more effective [43,44]. Also, Alami et al [45] and Elakhdar [11] indicated that Rhizobium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their excellent growth promotion and biocontrol activities P . aeruginosa isolated from the rhizosphere of crop plants and environmental samples can be used as inoculant for promotion of plant growth [ 54 56 ]. P .…”
Section: Discussionmentioning
confidence: 99%